2010
DOI: 10.1136/jmg.2010.084608
|View full text |Cite
|
Sign up to set email alerts
|

TMEM70 mutations are a common cause of nuclear encoded ATP synthase assembly defect: further delineation of a new syndrome

Abstract: The current report corroborates the previously described unique phenotype of TMEM70 deficiency. The study identifies TMEM70 gene defect as a pan-ethnic disorder and further redefines it as the most common cause of nuclear-origin ATP synthase deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 20 publications
3
39
1
3
Order By: Relevance
“…Pathogenic mutations to MTATP6 [92] can result in maternally inherited Leigh syndrome (MILS) [93] and neuropathy, ataxia, retinal pigmentosa (NARP) [90,92]. Additionally, mutations to CV assembly factors, TMEM70 [94] and ATPAF2 [95] have been identified and present with cardiomyopathy, hypotonia, intrauterine growth restriction and oligohydramnios [94,95] (Table 1).…”
Section: Oxphos Complex Vmentioning
confidence: 99%
“…Pathogenic mutations to MTATP6 [92] can result in maternally inherited Leigh syndrome (MILS) [93] and neuropathy, ataxia, retinal pigmentosa (NARP) [90,92]. Additionally, mutations to CV assembly factors, TMEM70 [94] and ATPAF2 [95] have been identified and present with cardiomyopathy, hypotonia, intrauterine growth restriction and oligohydramnios [94,95] (Table 1).…”
Section: Oxphos Complex Vmentioning
confidence: 99%
“…One individual with Type IV 3-methylglutaconic aciduria, had mild symptoms, but persistent hypertrophic cardiomyopathy was a feature [70]. In a second study, six new patients were identified with infantile onset cataracts, early gastrointestinal dysfunction, and congenital hypertonia with contractures resembling distal arthrogryposis [71].…”
Section: Mutations In Tmem70 and Complex V Deficiencymentioning
confidence: 98%
“…[6,7]. У всех пациентов выявляются выраженный лактат-ацидоз, гипераммониемия, во время кризов -гипераланиниемия и 3-метилглютаконовая ацидурия [4,5].…”
Section: клиническая картинаunclassified
“…2) в гетерози-готном состоянии, приводящая к сдвигу рамки считыва-ния p.Thr193Serfs*6. Мутации описаны ранее у пациен-тов с недостаточностью АТФ-синтетазы и неонатальной митохондриальной энцефалокардиомиопатией [4,6]. Обе мутации, выявленные методом массового парал-лельного секвенирования, подтверждены методом пря-мого автоматического секвенирования по Сэнгеру.…”
Section: клинический случайunclassified
See 1 more Smart Citation